A Rare Case of Orbital Cellulitis with Tolosa-Hunt Syndrome Caused by Methicillin-Resistant Staphylococcus aureus (MRSA): a Case Report - Bharata, Putu Evindya Vipascitadewi Nandanaya; Suryawati, Nyoman; Karna, Ratih Vibriyanti; Duarsa, Putu Laksmi Anggari Putri; Juliari, Gusti Ayu Made (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Orbital cellulitis is an active infection of the orbital soft tissue posterior to the orbital septum, which can cause Tolosa-Hunt Syndrome (THS) complication. Purpose: We reported a child with orbital cellulitis with THS complication caused by methicillin-resistant Staphylococcus aureus (MRSA). Case: A two-year-old girl complained of swelling and pain in the left eye accompanied by fever. In nasal region and left eye showed multiple erythema patches with geographic shape, size 1x2cm - 4x5cm, unclear border, erosion with sizes 0.5x1cm - 1x1.5 cm size covered with blackish crusts. After several days of hospitalization, she complained of proptosis and pain in moving her eye. We did the magnetic resonance imaging (MRI) scan examination, which showed a mass size of 2.2 x1.1 x 0.9 cm in a left intraconal orbital and dilation of the left-sided cavernous sinus. The blood culture showed MRSA bacteria. She was diagnosed with orbital cellulitis with THS complication and showed a good response with Meropenem, Methylprednisolone, cendo lyteers eye drops, levofloxacin eye drops, and gentamicin eye ointment. Discussion: Orbital cellulitis presents as ill-defined erythema, edema, warmth, and pain around the nasal and the orbital region and is more often found in children. The THS complication is characterized by ophthalmoplegia, unilateral orbital or periorbital pain, unilateral headache, and leukocytosis. Orbital cellulitis management includes antibiotic intravenous, corticosteroid, and eye care. Conclusion: THS is a rare complication of orbital cellulitis. Early diagnosis and management of orbital cellulitis are essential to prevent THS complication.